2011
DOI: 10.5897/ajb11.636
|View full text |Cite
|
Sign up to set email alerts
|

Thidiazuron: A multi-dimensional plant growth regulator

Abstract: Thidiazuron (TDZ) has gained a considerable attention during past decades due to its efficient role in plant cell and tissue culture. Wide array of physiological responses were observed in response to TDZapplication in different plant species. TDZ has shown both auxin and cytokinin like effects, although, chemically, it is totally different from commonly used auxins and cytokinins. A number of biological (physiological and biochemical) events in cells are induced or enhanced by TDZ, but the mode of action of T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
1
6

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 200 publications
(40 citation statements)
references
References 177 publications
(90 reference statements)
2
22
1
6
Order By: Relevance
“…PGRs that includes TDZ are yet unclear but, treatment with the concentrations had stimulated formation of nodular-green morphogenic callus in many plants [27,28]. In the present study, cultivation of C. fragrans callus cultures on medium added with 0.5 mg L -1 of the cytokinins did not induce a clear difference on callus morphology about PGRs-free media.…”
Section: In Vitro Morphogenesiscontrasting
confidence: 45%
“…PGRs that includes TDZ are yet unclear but, treatment with the concentrations had stimulated formation of nodular-green morphogenic callus in many plants [27,28]. In the present study, cultivation of C. fragrans callus cultures on medium added with 0.5 mg L -1 of the cytokinins did not induce a clear difference on callus morphology about PGRs-free media.…”
Section: In Vitro Morphogenesiscontrasting
confidence: 45%
“…These data corroborate those reported by Murthy et al (1998) and Corredoira et al (2008) indicating the morphoregulatory potential of TDZ and its application in plant tissue culture for the development of micropropagation systems. The reasons for the high activity of TDZ in woody species have not been investigated at a physiological level but it was suggested that TDZ helps to establish the optimal internal balance growth regulators (Saxena, 1992;Guo et al 2011).…”
Section: Resultsmentioning
confidence: 99%
“…1t-w). In many reported studies in the literature lower levels of the TDZ was found sufficient for stimulating shoot organogenesis from cotyledonary explant while higher concentrations promoted SE [28]. Cultivation of rhizogenic callus cultures on medium supplemented with lower levels of the TDZ stimulated shoot formation and SE at low frequency [29] while it promoted formation of embryogenic callus from root tip, stem and leaf segments explants [30].…”
Section: In Vitro Morphogenesismentioning
confidence: 99%